A prospective, open-label, randomized trial of doxycycline versus azithromycin for the treatment of uncomplicated murine typhus - Newton, P; Keolouangkhot, V; Lee, S; Choumlivong, K; Sisouphone, S; Choumlivong, K; Vongsouvath, M; Mayxay, M; Chansamouth, V; Davong, V; Phommasone, K; Sirisouk, J; et al. (Oxford University Press, 2018)
Background Murine typhus, or infection with Rickettsia typhi, is a global but neglected disease without randomised clinical trials to guide antibiotic therapy. Doxycycline is commonly used but without objective evidence for optimum treatment duration. Azithromycin is a potential alternative. Methods A prospective, open, randomised trial was conducted in non-pregnant, consenting inpatient adults with rapid diagnostic test evidence for uncomplicated murine typhus at two hospitals in Vientiane, Laos. Patients were randomised to seven (D7) or three days (D3) oral doxycycline or three days oral azithromycin (A3). Primary outcome measures were fever clearance time (FCT) and frequencies of treatment failure and relapse. Trial registration ISRCTN47812566. Results Between 2004-2009, 216 patients (72 per arm) were enrolled; 158 (73.2%) patients had serology/PCR-confirmed murine typhus; 52 (24.1%) were R. typhi PCR-positive. All patients survived to discharge. One patient in each treatment group withdrew. Treatment failure risk was greater following regimen A3 (22.5%, 16/71) compared to D3 (4.2%, 3/71) or D7 (1.4%, 1/71)(p<0.0001). The area under the time-fever curve and FCT, for R. typhi PCR-positive patients, was significantly higher in patients following A3 than D3 (1.8 fold and 1.9 fold, respectively) and D7 (1.5 fold and 1.6 fold, respectively)(p=0.005 & p=0.021). No patients returned with PCR-confirmed R. typhi relapse. Conclusion In Lao adults azithromycin is inferior to doxycycline for the oral therapy of uncomplicated murine typhus. Three and seven days of doxycycline have similar efficacy. Azithromycin use in murine typhus should be reconsidered. Investigation of genomic and phenotypic markers of R. typhi azithromycin resistance is needed.